PENERAPAN ALGORITMA KLASIFIKASI NAÃVE BAYES UNTUK ANALISIS SENTIMEN TENTANG PEMINDAHAN IBU KOTA NEGARA - Abdul Halim Hasugian; Raissa Amanda Putri; Mulya Alfan Simatupang (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: The decision of the Government of the Republic of Indonesia regarding the relocation of the territory of the Indonesian state capital to the Nusantara Capital in North Penajam Pasir, East Kalimantan is certainly an interesting discussion. This is a new record in Indonesian history because it has never happened before, becoming one of the big news stories that has generated a lot of opinions or reactions from the public. Twitter is one of the social media that people use to express opinions. Various kinds of opinions, both positive and negatif, are expressed by Indonesian people through their Twitter social media accounts. The data was obtained by crawling techniques from social media Twitter with the keywords "ibu kota nusantara" and "ikn" with the amount of data used as many as 606 tweets. The data is then labeled (class) using the lexicon-based method but first translated into English so that it is detected by the lexicon dictionary. From the labeling results, there were 400 tweets (66%)Â  with positive labels and 206 tweets (34%) with negatif labels. The data preprocessing stage is carried out in preparation for the data to be processed for sentimen analysis. Of the many opinions obtained, an analysis of public opinion sentimen about the relocation of the national capital will be carried out using the NaÃ¯ve Bayes classification algorithm. This study also applied the TF-IDF word weighting method with the n-gram feature used, namely bigram (n=2). The system will be evaluated using a confusion matrix. The performance of the system built in this study can be said to be good.Â Keywords: relocation of national capitals; sentiment analysis; naÃ¯ve bayes classifier.Â Abstrak: Keputusan Pemerintah Republik Indonesia tentang pemindahan wilayah ibu kota negara Indonesia menjadi Ibu Kota Nusantara di Penajam Pasir Utara, Kalimantan Timur tentu menjadi pembahasan yang menarik. Ini merupakan catatan baru dalam sejarah Indonesia karena belum pernah terjadi sebelumnya, menjadi salah satu berita besar yang menimbulkan banyak opini atau reaksi dari masyarakat. Twitter merupakan salah satu media sosial yang digunakan masyarakat untuk mengungkapkan opini. Berbagai macam opini antara positif dan negatif diutarakan masyarakat Indonesia melalui akun media sosial Twitternya. Data diperoleh dengan teknik crawling dari media social Twitter dengan kata kunci â€œibu kota nusantaraâ€ dan â€œiknâ€ dengan jumlah data yang digunakan sebanyak 606 tweet. Data kemudian diberi label (kelas) dengan metode lexiconÂ¬-based tetapi terlebih dahulu menerjemahkannya kedalam Bahasa Inggris agar terdeteksi oleh kamus leksikon. Dari hasil pelabelan diperoleh data berlabel positif sebanyak 400 tweet (66%) dan negatif sebanyak 206 tweet (34%) . Tahap preprocessing data dilakukan sebagai persiapan untuk data agar bisa diproses untuk analisis sentimen. Dari sekian banyak opini yang diperoleh, maka akan dilakukan analisis sentimen opini masyarakat tentang pemindahan ibu kota negara dengan menggunakan algoritma klasifikasi NaÃ¯ve Bayes. Pada penelitian ini juga diterapkan metode pembobotan kata TF-IDF dengan fitur n-gram yang digunakan yaitu bigram (n=2). Sistem akan dievaluasi dengan menggunakan confusion matrix. Kinerja dari sistem yang dibangun pada penelitian ini dapat dikatakan baik.Â Kata kunci: pemindahan ibu kota negara; analisis sentimen; naÃ¯ve bayes classifier.